LAYANAN PERPUSTAKAAN KHUSUS INSTANSI/ LEMBAGA PEMERINTAH: TINJAUAN RINGKAS - Utami Budi Rahayu Hariyadi (Jurnal IPI (Ikatan Pustakawan Indonesia), 2014)
This article is a brief overview of the defiifion, duties, and functions of the services as well as specific aspect in library monagement activities within the context of government departments. The author uses Guidelines far Libraries of Government Departements published by IFLA in 2008 and olso on Standar Nasional Indonesia (SNI) 7466:2009 about special libraries government department as a reference. Libraries need to be managed by government department librarians and library staff are competent and are always improving their skills in accordance with the development of the application of information ond cammunication & technology for libraries.